SUDDEN DEATH SYNDROME CAUSED BY CARDIAC TUMOR - Petrovic Rodic, Dusica (Medicinski časopis, 2020)
Cardiac tumors are not a common pathology. However, due to their occurrence in the vital organ, they bare an extremely important clinical significance. According to biological behavior, they are divided into 2 groups, primary (benign and malignant), which are less frequent and secondary (metastatic), which are more common. Among all primary benign cardiac tumors, myxoma is the one that occurs most often. A great number of studies indicate that it originates from multipotent mesenchymal cells of the septum of the left atrium. It is due to its localization that some authors consider it potentially malignant. This paper presents a case of cardiac myxoma which is echocardiographically diagnosed in a 34-year-old woman who died suddenly, several days before the scheduled surgery. The diagnosis of the disease was confirmed after the autopsy, by a routine haematoxylin-eosin (H&E) staining method and an additional immunohistochemistry method (IHC). By presenting a rare clinical case, we emphasize the fact that every diagnosed cardiac tumor requires immediate cardiac surgery without delay.